Rare bird documentation form for Peregrine Falcon at Willow Slough, 1984 - Wilson, Barbara L.et al (1984)
Rare bird documentation form for a Peregrine Falcon at Willow Slough in Mills County, IA on April 24, 1984. Epson - sheet feed/flatbed